2019
DOI: 10.1016/j.forsciint.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evaluation of spring powered air rifle storage and modifications on forensic practice and casework

Abstract: Air weapons are commonly used by civilian populations across the world, particularly by those under 18, and discharges often result in desecration, criminal damage and animal abuse. Online forums and websites provide an accessible resource for civilians to access airgun modification methods proposing to increase muzzle velocity. However, there is limited published research that empirically evaluates the impact of air weapon modification and the potential to influence casework interpretation. Therefore, this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…By using a small number of break barrel, spring powered air rifles for their study, they found a significant variation in muzzle velocities as a result of the two earlier mentioned modifications. They also found that the orientation of storing (vertically) and/or cocking statistically effected the consistency of recorded muzzle velocities, reinforcing the requirement to undertake the weapon examination in short order [ 100 ].…”
Section: Methodsmentioning
confidence: 99%
“…By using a small number of break barrel, spring powered air rifles for their study, they found a significant variation in muzzle velocities as a result of the two earlier mentioned modifications. They also found that the orientation of storing (vertically) and/or cocking statistically effected the consistency of recorded muzzle velocities, reinforcing the requirement to undertake the weapon examination in short order [ 100 ].…”
Section: Methodsmentioning
confidence: 99%